1996
DOI: 10.1016/0014-5793(96)00583-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein import into the nucleus

Abstract: The transport of proteins from the cytoplasm into the nucleus is a multistep process. The nuclear localization sequence (NLS) of a transport substrate associates with the heterodimeric NLS-receptor which binds to a subset of proteins of the nuclear pore complex (NPC). Translocation through the NPC is energydependent and requires the small GTPase Ran. Proteins that interact with Ran in either the GDP-bound or the GTP-bound state coordinate transfer through the NPC. Lastly, the NLSreeeptorlsubstrate complex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 83 publications
(147 reference statements)
0
41
0
Order By: Relevance
“…RanBP1 contains a RanGTP-binding domain different from that of importin ␤. Yrb1p, the yeast homologue of RanBP1, is an essential cytoplasmic protein which is required for nucleocytoplasmic transport (reviewed in reference 61).…”
mentioning
confidence: 99%
“…RanBP1 contains a RanGTP-binding domain different from that of importin ␤. Yrb1p, the yeast homologue of RanBP1, is an essential cytoplasmic protein which is required for nucleocytoplasmic transport (reviewed in reference 61).…”
mentioning
confidence: 99%
“…The Ran protein (Ras-related nuclear protein) is a member of the Ras superfamily of small nuclear GTPase, which is believed to be involved in normal cell cycle progression and in the transport of RNA and proteins between the nucleus and cytoplasm [2,[13][14][15][16]. Proteins interact with Ran at the GDP-or GTP-bound state, thereby regulating their transport through NPCs [27].…”
mentioning
confidence: 99%
“…Immunoelectron microscopy has demonstrated that RanBP2/Nup358 localizes to the cytoplasmic fibrils [21,22,[35][36][37], whereas Nupl53 and Nup98 are constit uents of the nuclear basket [18,22,38,39]. These find ings have provided the basis for several transport mod els in which FG-repeat-containing nucleoporins form a static array of docking sites that transiently interact with transport complexes [8,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Protein import into the nucleus is mediated by a heterodimer comprising the nuclear localization sig nal (NLS)-receptor/importin a, which recognizes the NLSs of karyophilic proteins, and nuclear import fac tor p97/importin /?, which contacts the NPC [re viewed by 6; see also [7][8][9], After this first docking step, the ligand complex is imported via an energydependent process th a t requires the small GTPase Ran/TC4 [10,11]. GTP hydrolysis by Ran is though to drive the translocation reaction [12][13][14], which may involve repeated association and dissociation of im port complex components to the NPC [15,16], or the movement of a single complex across the NPC either in discrete steps [17] or in a sliding motion [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation